Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Cumulative Review: 37c



Work Step by Step

We are given that $f(x)=x-1$ and $g(x)=2x-3$. We know that $(f\times g)(x)=f(x)\times g(x)$. Therefore, $(f\times g)(x)=f(x)\times g(x)=(x-1)(2x-3)$. We can use the FOIL method to simplify. F=$x\times 2x=2x^{2}$ O=$x\times-3=-3x$ I= $-1\times2x=-2x$ L=$-1\times-3=3$ Next, we can add these terms together. $(2x^{2})+(-3x)+(-2x)+(3)=2x^{2}-5x+3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.